Demonstration of Heterogeneous Parahydrogen Induced Polarization Using Hyperpolarized Agent Migration from Dissolved Rh(I) Complex to Gas Phase - Kovtunov, Kirill V. (American Chemical Society, 2014)
[Image: see text] Parahydrogen-induced polarization (PHIP) was used to demonstrate the concept that highly polarized, catalyst-free fluids can be obtained in a catalysis-free regime using a chemical reaction with molecular addition of parahydrogen to a water-soluble Rh(I) complex carrying a payload of compound with unsaturated (C=C) bonds. Hydrogenation of norbornadiene leads to formation of norbornene, which is eliminated from the Rh(I) complex and, therefore, leaves the aqueous phase and becomes a gaseous hyperpolarized molecule. The Rh(I) metal complex resides in the original liquid phase, while the product of hydrogen addition is found exclusively in the gaseous phase based on the affinity. Hyperpolarized norbornene (1)H NMR signals observed in situ were enhanced by a factor of approximately 10 000 at a static field of 47.5 mT. High-resolution (1)H NMR at a field of 9.4 T was used for ex situ detection of hyperpolarized norbornene in the gaseous phase, where a signal enhancement factor of approximately 160 was observed. This concept of stoichiometric as opposed to purely catalytic use of PHIP-available complexes with an unsaturated payload precursor molecule can be extended to other contrast agents for both homogeneous and heterogeneous PHIP. The Rh(I) complex was employed in aqueous medium suitable for production of hyperpolarized contrast agents for biomedical use. Detection of PHIP hyperpolarized gas by low-field NMR is demonstrated here for the first time.